Seasonality of trichinellosis in patients hospitalized in Belgrade, Serbia* - Ofori-Belić I.; Korać M.; Milošević B.; Djurković-Djaković O.; Dulović O.; Dakić Z.; Poluga J.; Brmbolić B. (Parasite, 2010)
A retrospective study of the course and outcome of trichinellosis in a series of 50 patients hospitalized at the Institute for Infectious and Tropical Diseases in Belgrade between 2001 and 2008 was performed. Clinical diagnosis of trichinellosis was based upon the patients’ clinical history, symptoms and signs, and eosinophilia. The occurrence of cases showed a strong seasonality (P < 0.0001). The incubation period ranged between one and 33 days. The mean time between onset of symptoms and admission was nine days. Family outbreaks were the most frequent. Smoked pork products were the dominant source of infection (76 %). Fever was the most frequent clinical manifestation (90 %), followed by myalgia (80 %) and periorbital edema (76 %). 43 patients were examined serologically and 72 % of them had anti-Trichinella antibodies. Eosinophilia and elevated levels of serum CK and LDH were detected in 94, 50 and 56 % of the patients, respectively. All patients responded favorably to treatment with mebendazole or albendazole, but eight developed transient complications. Trichinellosis remains a major public health issue in Serbia.